Analysis of position promotion that influence employee employee at the department of investment and one door integrated missioning services, simalungun regency - Ben Setiawan; Adrian K Tarigan; Diana Florenta Butar – Butar; Demak Manik; Suwita (Enrichment : Journal of Management, 2022)
The role of local government in facilitating the development of investment is needed to create efficiency and a climate conducive to investment. These efforts cannot be separated from the role of the One-Stop Investment and Integrated Services Service (DPMPTSP) to continue to make strategies through new innovations in improving licensing and investment services. From the results of the partial research on promotion variables, it can be seen that the indicator that has the most dominant influence on employee morale at the Investment and One-Stop Integrated Licensing Service Office, Simalungun Regency, Simalungun Regency is work performance (X 2 ) . So the hypothesis that says there is a significant influence simultaneously on the promotion variable which includes the availability of experience (X 1 ), work performance (X 2 ), responsibility (X 3 ), initiative (X 4 ), sociability (X 5 ), on morale employee work at the Simalungun District One Integrated Investment and Licensing Services Service is acceptable.